Driving under the (cellular) influence - Bhargava, Saurabh (2013)
Investigates the causal link between driver cell phone use and crash rates by exploiting a natural experiment induced by the change in cellular plans - a discontinuity in the marginal price of a phone call at 9pm on weekdays.